Plasma Exchange-Based Non-bioartificial Liver Support System Improves the Short-Term Outcomes of Patients With Hepatitis B Virus-Associated Acute-on-Chronic Liver Failure: A Multicenter Prospective Cohort Study - Chen, Yuan-yuan; Li, Hai; Xu, Bao-yan; Zheng, Xin; Li, Bei-ling; Wang, Xian-bo; Huang, Yan; Gao, Yan-hang; Qian, Zhi-ping; Liu, Feng; Lu, Xiao-bo; Shang, Jia; et al. (Frontiers in Medicine, 2021)
Background & Aims: Hepatitis B virus-associated acute-on-chronic liver failure (HBV-ACLF) is a complicated syndrome with extremely high short-term mortality. Whether plasma exchange (PE) improves HBV-ACLF outcomes remains controversial. Here, PE-based nonbioartificial liver support system (NB-ALSS) effects on short-term HBV-ACLF patient outcomes were investigated. Materials and Methods: HBV-ACLF patients from Chinese Acute-on-chronic Liver Failure (CATCH-LIFE) cohort receiving standard medical therapy (SMT) alone or PE-based NB-ALSS in addition to SMT were allocated to SMT and SMT+PE groups, respectively; propensity score matching (PSM) was used to eliminate confounding bias. Short-term (28/90-day and 1-year) survival rates were calculated (Kaplan-Meier). Results: In total, 524 patients with HBV-ACLF were enrolled in this study; 358 received SMT alone (SMT group), and the remaining 166 received PE-based NB-ALSS in addition to SMT (SMT+PE group). PSM generated 166 pairs of cases. In the SMT+PE group, 28-day, 90-day and 1-year survival rates were 11.90%, 8.00% and 10.90%, respectively, higher than those in the SMT group. Subgroup analysis revealed that PE-based NB-ALSS had the best efficacy in patients with ACLF grade 2 or MELD scores of 30 to 40 (MELD grade 3). In MELD grade 3 patients who received SMT+PE, 28-day, 90-day and 1-year survival rates were improved by 18.60%, 14.20% and 20.10%, respectively. According to multivariate Cox regression analysis, PE-based NB-ALSS was the only independent protective factor for HBV-ACLF patient prognosis at 28 days, 90 days, and 1 year (28 days, HR = 0.516, p = 0.001; 90 days, HR = 0.663, p = 0.010; 1 year, HR = 0.610, p = 0.051). For those who received SMT+PE therapy, PE-based NB-ALSS therapy frequency was the only independent protective factor for short-term prognosis (28-day, HR = 0.597, p = 0.001; 90-day, HR = 0.772, p = 0.018). Conclusions: This multicenter prospective study showed that the addition of PE-based NB-ALSS to SMT improves short-term (28/90 days and 1-year) outcomes in patients with HBV-ACLF, especially in MELD grade 3 patients. Optimization of PE-based NB-ALSS may improve prognosis or even save lives among HBV-ACLF patients.